College students' perceptions of risk and addictiveness of e-cigarettes and cigarettes. Issue 2 (17th February 2017) - Cooper, Maria; Loukas, Alexandra; Harrell, Melissa B.; Perry, Cheryl L.
ABSTRACT: Background: As conventional cigarette use is declining, electronic cigarette ("e-cigarette") use is rising and is especially high among college students. Few studies examine dual use of e-cigarettes and cigarettes among this population. This study explores the relationship between dual and exclusive e-cigarette / cigarette use and perceptions of harm and addictiveness of both products.Methods: This is a cross-sectional analysis of data from students attending 24 colleges in Texas (n=5, 482). Multinomial logistic regression was employed to test the association between current e-cigarette / cigarette use and perceived harm and addictiveness of both products. Three tobacco groups were included: cigarette only users, e-cigarette only users, and dual users.Results: Dual users reported lower perceived harm of e-cigarettes most consistently (p<0.001, all comparisons). Perceived harm of cigarettes was significantly lower among cigarette only and dual users only, compared to non-users (p<0.001, all comparisons). Compared to non-users, all three groups reported significantly lower perceived addictiveness of e-cigarettes (p<0.001, all comparisons). The same finding was observed for perceived addictiveness of cigarettes, though findings were less consistent for the e-cigarette only group (p<0.02, all comparisons except one).Conclusion: Findings demonstrate that among college students, perceptions of harm and addictiveness of e-cigarettes are lower than those for conventional cigarettes. For both products, perceptions of harm and addictiveness were lower among exclusive and dual users, compared to non-users.